PENERAPAN SISTEM INFORMASI AKUNTANSI BERBASIS MICROSOFT EXCEL PADA UMKM TELLU SILO’ DI KABUPATEN SINJAI - Darwis, Marina; S, Masnawaty; Afiah, Nur (Jurnal Sains Riset, 2024)
This research aims to apply a Microsoft Excel-based information system to Tellu Silo' MSMEs to support business development in accordance with accounting reporting. The data collection methods used were interviews and documentation. The data analysis design used in this research is descriptive qualitative. The population in this research is Tellu Silo' MSMEs in Sinjai Regency. The sample in this research is data on cash receipts and disbursements at Tellu Silo' MSMEs in 2022. The results of research on Tellu Silo' MSMEs are that they do not always record transactions that occur and the recording is still done manually and simply. This will cause problems with financial reports such as cash received not being in accordance with recording, losses, etc. With this SIA, researchers hope that it can help facilitate the recording and presentation of financial reports.